Effects of Temperature on Intraspecific Competition in Ectotherms - Amarasekare, Priyanga; Coutinho, Renato M. [UNESP] (Univ Chicago Press, 2014)
Understanding how temperature influences population regulation through its effects on intraspecific competition is an important question for which there is currently little theory or data. Here we develop a theoretical framework for elucidating temperature effects on competition that integrates mechanistic descriptions of life-history trait responses to temperature with population models that realistically capture the variable developmental delays that characterize ectotherm life cycles. This framework yields testable comparative predictions about how intraspecific competition affects reproduction, development, and mortality under alternative hypotheses about the temperature dependence of competition. The key finding is that ectotherm population regulation in seasonal environments depends crucially on the mechanisms by which temperature affects competition. When competition is strongest at temperatures optimal for reproduction, effects of temperature and competition act antagonistically, leading to more complex dynamics than when competition is temperature independent. When the strength of competition increases with temperature past the optimal temperature for reproduction, effects of temperature and competition act synergistically, leading to dynamics qualitatively similar to those when competition is temperature independent. Paradoxically, antagonistic effects yield a higher population floor despite greater fluctuations. These findings have important implications for predicting effects of climate warming on population regulation. Synergistic effects of temperature and competition can predispose populations to stochastic extinction by lowering minimum population sizes, while antagonistic effects can increase the potential for population outbreaks through greater fluctuations in abundance.
Keywords: ectotherm; intraspecific competition; population dynamics; seasonality; temperature; temperature variation